1998
DOI: 10.2343/geochemj.32.71
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of oxygen diffusivity from anion porosity in minerals.

Abstract: An empirical model for predicting oxygen diffusivity from anion porosity is presented for a wide range of minerals. It is based on the examination of experimental diffusion data under anhydrous and hydrothermal conditions. The relationship between activation energies and pre-exponential factors in all minerals is assumed to obey a common compensation law regardless of diffusion medium (H20, OH-, CO2 or 02). However, the H20 molecules and OH groups are relatively small in volume and thus can migrate within mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
9

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(85 citation statements)
references
References 65 publications
4
72
0
9
Order By: Relevance
“…The activation energy for oxygen diffusion in uraninite (123.4 kJ/mol) obtained in our study is similar to those calculated by Auskern and Belle (1961) for UO 2.004 and UO 2.063 (124.3 kJ/mol), but significantly different from the activation energy calculated for UO 2.002 (273.2 kJ/mol; Fig. 6) as well as the activation energies calculated theoretical by Zheng and Fu (1998) for dry diffusion (246.9 kJ/ mol) and wet diffusion (167.4 kJ/mol). This suggests that previous experimental data represent only volume diffusion and that oxygen diffusion processes during gas-solid or solid-solid interactions are not similar to those during hydrous fluid-mineral interactions at temperatures between 400 and 700°C.…”
Section: Oxygen Diffusionsupporting
confidence: 73%
“…The activation energy for oxygen diffusion in uraninite (123.4 kJ/mol) obtained in our study is similar to those calculated by Auskern and Belle (1961) for UO 2.004 and UO 2.063 (124.3 kJ/mol), but significantly different from the activation energy calculated for UO 2.002 (273.2 kJ/mol; Fig. 6) as well as the activation energies calculated theoretical by Zheng and Fu (1998) for dry diffusion (246.9 kJ/ mol) and wet diffusion (167.4 kJ/mol). This suggests that previous experimental data represent only volume diffusion and that oxygen diffusion processes during gas-solid or solid-solid interactions are not similar to those during hydrous fluid-mineral interactions at temperatures between 400 and 700°C.…”
Section: Oxygen Diffusionsupporting
confidence: 73%
“…Of course, oxygen-self diffusion in carbonates and the singleton diffusion component of clumped isotope reordering are not equivalent processes; indeed, the rates of these two processes are different in natural systems , and the former is strongly dependent on fH2O while a dependence in the latter has not yet been observed outside of uncertainty (Passey et al, 2012;Brenner et al, 2018). Instead, we merely note that the order of ∆47 reordering rates in calcite, dolomite, and magnesite suggested by the apparent equilibrium blocking temperatures in natural carbonates (del Real et al, 2016;Lloyd et al, 2017), and corroborated by this study, is consistent with the ranking of ion porosities in these three related phases (Fortier and Giletti, 1989;Zheng and Fu, 1998). Moreover, it is noteworthy that the isokinetic temperature for elemental diffusion in carbonates-i.e., the temperature at which diffusivities of all species converge-is 690 °C (Brady and Cherniak, 2010), which is in good agreement with the temperature at which kdiff,single in calcite and dolomite are indistinguishable (~700°C; Fig.…”
Section: Comparisons With Calcite Reordering Parameterssupporting
confidence: 72%
“…Experimental data for carbonates other than calcite are limited, but suggest that diffusivities of the same species are systematically slower in dolomite (Anderson, 1972). This ordering is consistent with the predictions of the anion porosity model of Zheng and Fu (1998), wherein the tighter packing of anions in dolomite unit cells results in increases in the activation energy and pre-exponential factor for oxygen self-diffusion in this phase. Of course, oxygen-self diffusion in carbonates and the singleton diffusion component of clumped isotope reordering are not equivalent processes; indeed, the rates of these two processes are different in natural systems , and the former is strongly dependent on fH2O while a dependence in the latter has not yet been observed outside of uncertainty (Passey et al, 2012;Brenner et al, 2018).…”
Section: Comparisons With Calcite Reordering Parameterssupporting
confidence: 66%
“…To date, numerous studies have shown that the MNR is upheld not only for many diffusing species in individual minerals (Hart 1981), but also for a single diffusing species in a wide variety of minerals (Béjina and Jaoul 1997;Zheng and Fu 1998;Zhao and Zheng 2007;Zhang et al 2010Zhang et al , 2011Brady and Cherniak 2010;Jones 2014;Zhang and Shan 2015a, b). Recently, based on the observed MNR, a thermodynamic model (the so-called cBX model) has been successfully applied to predict diffusion coefficients of various elements in silicate minerals (Zhang et al , 2011Zhang 2012;Zhang and Shan 2015a, b).…”
Section: Diffusion Compensation Lawmentioning
confidence: 99%